KARAKTERVEGETATIF DAN PRODUKSI AWAL TANAMAN JARAK PAGAR (JATROPHA CURCAS L.) AKIBAT PERLAKUAN MUTAGEN COLCHICINE - Agus Zainudin (Jurnal Gamma, 2010)
Mutation and polyploidization represent some of plant breeding method exploited to increasegenetic diversity of physic nut. The result of mutation polyploidization process obtainable superiorphysic nut polyploid. This research was aimed to study the appearance of physic nut effected byconcentration and frequency of colchicine treatment. The type of physic nut used in this research isIP-1A. The combination of concentration colchicine (0,1%; 0,2%; 0,3%; 0,4%; 0,5%; 0,6%) andfrequency of colchicine solution (6 times, 8 times, 10 times) treated to get a mutant of physic nut.Plant without colchicine as a control. The result of this research indicated that the colchicine causevariation at vegetatif character. There is 3-5 crops having vegetatif size higher than control crop.Treatment of colchicine 0,5% 6x; 0,3% 10x and 0,2% 8x yields higher maximum fruit that is 95-168 fruits compared to control crop yielding 89 fruits.Key words : Physic nut, polyploid, mutation, colchicines